Mandible Reconstruction With Custom-Made Plates in Medication-Related Osteonecrosis of the Jaw—A Case Series - Eiji Mitate; Taichi Demura; Youta Yamauchi; Yasuhisa Sawai; Miho Hasumoto; Satoshi Wada; Hiroyuki Nakano; Noboru Demura (Case Reports in Dentistry)
Conclusions: In conclusion, the use of completely customized reconstruction plates obviates the need for bending and other adaptations, reduces surgical time, and improves postoperative aesthetics. Of significance, preparing completely customized reconstruction plate requires about 3 weeks; thus, careful case selection and scheduling are indispensable.